BUNDLING PRODUCT AS A COOPERATION AGREEMENT BETWEEN BANKS AND INSURANCE COMPANIES (BANCASURRANCE) IN RELATIONS WITH UNHEALTHY BUSINESS COMPETITION - Rani Sri Agustina (Legal Standing : Jurnal Ilmu Hukum, 2019)
Banking institutions and insurance companies are two different finance institutions, both in terms of the type of business and in terms of the principles. The two of them undergo a cooperation (bancasurrance) through referential activities, distribution, and product integration. The cooperation activity of marketing integrated products is carried out by banks by offering and selling bundled products. Bundling is a marketing activity which is allowed, yet its implementation is almost the same as tying agreement, which is one of the prohibited agreements as it may lead to unhealthy business competition.